Characterization of peroxidase changes in tolerant and susceptible soybeans challenged by soybean aphid (Hemiptera: Aphididae) - Marchi-Werle, L. (2014)
Changes in protein content, peroxidase activity, and isozyme profiles in response to soybean aphid feeding were documented at V1 (fully developed leaves at unifoliate node, first trifoliate leaf unrolled) and V3 (fully developed leaf at second trifoliate node, third trifoliate leaf unrolled) stages of soybean aphid-tolerant (KS4202) and -susceptible (SD76R) soybeans. Protein content was similar between infested and control V1 and V3 stage plants for both KS4202 and SD76R at 6, 16, and 22 d after aphid introduction. Enzyme kinetics studies documented that control and aphid-infested KS4202 V1 stage and SD76R V1 and V3 stages had similar levels of peroxidase activity at the three time points evaluated. In contrast, KS4202 aphid-infested plants at the V3 stage had significantly higher peroxidase activity levels than control plants at 6 and 22 d after aphid introduction. The differences in peroxidase activity observed between infested and control V3 stage KS4202 plants at these two time points suggest that peroxidases may be playing multiple roles in the tolerant plant. Native gels stained for peroxidase were able to detect differences in the isozyme profiles of aphid-infested and control plants for both KS4202 and SD76R.